High-Intensity Interval Training Is Associated With Alterations in Blood Biomarkers Related to Brain Injury - Di Battista, Alex P.; Moes, Katherine A.; Shiu, Maria Y.; Hutchison, Michael G.; Churchill, Nathan; Thomas, Scott G.; Rhind, Shawn G. (Frontiers in Physiology, 2018)
Purpose: Blood biomarkers are a useful tool to study concussion. However, their interpretation is complicated by a number of potential biological confounds, including exercise. This is particularly relevant in military and athletic settings where injury commonly occurs during physical exertion. The impact of high-intensity interval training (HIIT) on putative brain-injury biomarkers remains under-examined. The purpose of this study was to observe the effects of HIIT on a panel of blood biomarkers associated with brain injury. Methods: Eleven healthy, recreationally active males (median age = 29.0, interquartile range = 26.0 – 31.5) performed HIIT on a bicycle ergometer (8-12 x 60-sec intervals at 100% of peak power output, interspersed by 75-sec recovery at 50 W) three times/week for two weeks. Peripheral blood samples were collected before and immediately after HIIT during the first and last training sessions. Plasma concentrations of s100 calcium binding protein beta (S100B), glial fibrillary acidic protein (GFAP), neuron-specific enolase (NSE), brain-derived neurotrophic factor (BDNF), neurogranin (NRGN), peroxiredoxin (PRDX)-6, creatine kinase-BB isoenzyme (CKBB), visinin-like protein (VILIP)-1, von Willebrand factor (vWF), monocyte chemoattractant protein (MCP)-1, matrix metalloproteinase (MMP)-9, and total tau (T-tau) were quantitated by high-sensitivity MULTI-SPOT® immunoassay, on the MesoScale Diagnostics electrochemiluminescence detection platform. Differences in biomarker concentrations in response to HIIT were evaluated by partial least squares discriminant analysis within a repeated-measures bootstrapped framework. Results: Ten of twelve biomarkers were increased pre-to-post HIIT; VILIP-1 remained unchanged, and GFAP was not statistically evaluated due to insufficient detectability. After two weeks of HIIT, T-tau was no longer significantly elevated pre-to-post HIIT, and significant attenuation was noted in the acute responses of NRGN, PRDX-6, MMP-9, and vWF. In addition, compared to session 1, at session 6 pre-exercise concentrations of NSE and VILIP-1 were significantly lower and higher, respectively. Conclusion: Blood biomarkers commonly associated with brain injury are significantly elevated in response to a single bout of HIIT. After a two-week, 6 session training protocol, this response was attenuated for some, but not all markers. While biomarkers continue to provide promise to concussion research, future studies are necessary to disentangle the common biological sequelae to both exercise and brain injury.